Balancing the supply and demand for taxonomy: An analysis of European taxonomic capacity and policy needs - Quentin J. Groom; Melanie De Nolf; Lina M. Estupinan-Suarez; Sofie Meeus (PLoS ONE, 2026)
Taxonomy is a cornerstone of biological science and essential to biodiversity policy, yet it faces persistent structural challenges collectively known as the “taxonomic impediment”. These include limited capacity, uneven geographic and taxonomic coverage, and a disconnect between the supply of expertise and its societal demand. In this study, we present a meta-research analysis of taxonomic activity in Europe over the past decade, drawing on publication metadata from OpenAlex, Wikidata, and GBIF. Using an open and reproducible workflow, we identify more than 31,000 authors affiliated with European institutions who have contributed to taxonomic publications, and we assess their taxonomic and institutional distribution. Using robust regression models, we show that biodiversity policy variables collectively explain additional variation in taxonomic research effort beyond species richness alone, with the Birds and Habitats Directives showing positive associations and marine-related policy variables showing negative associations. We explore how this supply of expertise compares with demands arising from European biodiversity policy, including legally binding instruments such as the Birds and Habitats Directives and the Marine Strategy Framework Directive, as well as strategic initiatives focused on invasive alien species, crop wild relatives, and species of conservation concern. Our results highlight clear imbalances in capacity across taxonomic groups and regions, with some politically and ecologically significant taxa receiving comparatively little attention. This work illustrates how openly available data can be used to evaluate taxonomic capacity and its alignment with policy needs, providing a framework for strategic planning and investment in taxonomy.